The Cinefication of the Painting of the 1920s: The OST Members’ Experience - Voronina, Oksana I. (Actual Problems of Theory and History of Art, 2018)
In this article the author aims to define the specifics of the contact between the painting by the Society of Easel Painters (OST; 1925-1932) and the rapidly developing cinematograph of the 1920s. The thesis analyzes the cinema devices that the OST members used to modernize easel painting. Primarily, they explicitly and implicitly expressed the montage principals of composition (notably “gluing” of blow-up and distant view), as well as the principals of “specific-typical” representation, attaching the same value to personages and things, etc. Cinefication determined the working technique of the OST members in numerous series of compositions with small variation of a motive. The OST artists also used the onscreen methods of vision objectification and the organization of viewer’s consciousness. The experience of documentary cinema and, in the first place, of Dziga Vertov was the closest to the practice of the OST group. The last one and the leader of the Kinoki group were interested not only in familiar motives, but also in the design of the pathetic picture of a new world. As for the approach to history, the OST members’ position was akin to the position of Sergei Eisenstein. By the example of the works by the OST artists, we can consider the problems of revitalizing Russian easel art during the 1920s in general. This paper is a work in progress. So further the question of interaction between the OST painting and cinematograph remains in the foreground of my research. Promising in this context is many-sided investigation of the specific time and spatial constructions and distinct illusionism in the OST compositions, which were considered as models for a new visual culture.